Between neutrality and perfection: Rawls's liberalism under scrutiny - Dalsotto, Lucas M (Sofia, 2026)
The article critically examines the tension between political neutrality and moral perfectionism within contemporary liberalism, with particular attention to Denis Coitinho’s (2024) proposal to reconcile both traditions through what he calls moderate perfectionist liberalism. Based on a brief reconstruction of the debate between Rawls (1993), Raz (1986), and other interpreters of liberalism, the paper argues that the internal coherence of liberal theory depends on a minimal ethical foundation. It is claimed that Rawls’ (1971; 1993) attempt to sustain political legitimacy without appealing to substantive conceptions of the good leads to a weakening of its own normativity, since neutrality, when understood as epistemic abstinence regarding moral truth, becomes self-contradictory. By distinguishing between political consensus and moral truth, the paper maintains that liberalism preserves its intelligibility only when it recognizes that values such as freedom, equality, and respect possess normative force independent of mere procedural agreement. From this diagnosis, the article contends that Coitinho’s hybridist project offers a promising alternative by affirming the complementarity between ethics and politics and conceiving public reason not merely as a neutral space of deliberation, but as a moral practice of mutual recognition.
Keywords: liberalism; perfectionism; neutrality; public reason; Denis Coitinho